Cow manure as additive to a DMBR for stable and high-rate digestion of food waste: Performance and microbial community. (1st January 2020) - Xing, Bao-Shan; Han, Yule; Wang, Xiaochang C.; Ma, Jing; Cao, Sifan; Li, Qian; Wen, Junwei; Yuan, Honglin
Abstract: Cow manure (CM) was added to a dynamic membrane bioreactor (DMBR) operated under anaerobic condition for enhancing food waste (FW) digestion for over 300 days with stepwise increase of organic loading rates (OLRs) from 1.07 to 11.9 g COD/L/day. At a FW/CM ratio of 3.5:1 (based on volatile solids), the mixed liquor pH was always above 8.0 and no apparent volatile fatty acids (VFAs) accumulation occurred even at the highest OLR of 11.9 g COD/L/day (hydraulic retention time as 10 days and solid retention time as 15.5 days, correspondingly), indicating a very stable operation condition which resulted in an average CH4 yield as high as 250 mL/g COD and CH4 production as high as 2.71 L CH4 /L/day. The hardly biodegradable organic components, such as cellulose, hemicellulose, and lignin, were effectively degraded by 78.3%, 58.8%, and 47.5%, respectively. Significantly high anaerobic digestion reaction ratios, especially the hydrolysis ratio which is usually the limiting factor, were calculated based on experimental results. Furthermore, the high lignocellulase contents and coenzyme F420 levels, along with the decrease of cellulose crystallinity from 72.6% to 16.4% in the feedstock, provided strong evidence of an enhanced biological activity by CM addition. By high-throughput sequencing analysis, more abundant and diverse bacterial, archaeal, and fungal genera were identified from the DMBR sludge. With CM addition, the biodegradation of lignocellulose might have produced sufficient H2 and CO2 for the hydrogenotrophic methanogens such as Methanoculleus, Methanomassiliicoccus, and Methanobacterium, which were highly tolerant to ammonium inhibition, and then the elevated ammonium level would have provided high buffering capacity in the DMBR thus ensuring a stable condition for high rate FW digestion and CH4 production. Graphical abstract: Image 1 Highlights: Long-term operation of a DMBR was conducted for FW digestion with CM as additive. Steady pH and low VFA level were maintained with increasing OLR to 11.9 g COD/L/day. CH4 production continuously increased with increasing OLR up to 2.71 L/L/day. More abundant and diverse bacteria, archaea and fungi were detected with CM addition.